Awake Craniotomy and Memory Induction Through Electrical Stimulation: Why Are Penfield's Findings Not Replicated in the Modern Era?. Issue 2 (8th January 2020) - Curot, Jonathan; Roux, Franck-Emmanuel; Sol, Jean-Christophe; Valton, Luc; Pariente, Jéremie; Barbeau, Emmanuel J
Abstract: From the 1930s through the early 1960s, Wilder Penfield 12 collected a large number of memories induced by electrical brain stimulation (EBS) during awake craniotomy. As a result, he was a major contributor to several neuroscientific and neuropsychological concepts of long-term memory. His 1963 paper, which recorded all the cases of memories he induced in his operating room, remains a substantial point of reference in neuroscience in 2019, although some of his interpretations are now debatable.  However, it is highly surprising that, since Penfield's 12 reports, there has been no other surgical publication on memories induced during awake surgery. In this review, we explore this phenomenon and analyze some of the reasons that might explain it. We hypothesize that the main reasons for lack of subsequent reports are related to changes in operative procedures (ie, use of anesthetics, time constraints, and insufficient debriefings) and changes in EBS parameters, rather than to the sites that are stimulated, the pathology treated, or the tasks used. If reminiscences are still induced, they should be reported in detail to add valuable contributions to the understanding of long-term memory networks, especially memories that are difficult to reproduce in the laboratory, such as autobiographical memories.